Susceptibilidade de Aedes aegypti aos inseticidas temephos e cipermetrina, Brasil Susceptibility of Aedes aegypti to temephos and cypermethrin insecticides, Brazil - Jonny E Duque Luna; Marcos Ferrer Martins; Adriana Felix dos Anjos; Eduardo Fumio Kuwabara; Mário Antônio Navarro-Silva (Universidade de São Paulo, 2004)
Realizaram-se bioensaios para detectar a susceptibilidade de Aedes aegypti aos inseticidas químicos, temefós e cipermetrina. Os resultados mostraram que esta espécie é suscetível a temefós e apresenta resistência a cipermetrinae. Bioassays were performed in order to detect the susceptibility of Aedes aegypti to the chemical insecticides temephos and cypermethrin. The results showed that this species is susceptible to temephos and presents resistance to cypermethrin.